Effects of different mean arterial pressure targets on plasma volume, ANP and glycocalyx—A randomized trial. Issue 2 (5th October 2020) - Damén, Tor; Saadati, Sofia; Forssell‐Aronsson, Eva; Hesse, Camilla; Bentzer, Peter; Ricksten, Sven‐Erik; Nygren, Andreas
Abstract: Background: Arterial haematocrit (Hct) has been shown to decrease after anaesthesia induction, most probably because of an increased plasma volume (PV). The primary objective was to quantify change in PV if mean arterial pressure (MAP) was kept at baseline level or allowed to decrease to 60 mm Hg. Our secondary objective was to evaluate underlying mechanisms of this response. Methods: Twenty‐four coronary artery bypass patients were randomized to a higher (90 mm Hg, intervention group) or lower (60 mm Hg, control group) MAP by titration of norepinephrine. During the experimental procedure, no fluids were administered. Baseline PV was measured by 125 I‐albumin and the change in PV was calculated from the change in Hct. Changes in MAP, plasma 125 I‐albumin, colloid osmotic pressure, albumin, Mid Regional‐pro Atrial Natriuretic Peptide (MR‐proANP) and endothelial glycocalyx components were measured from baseline to 50 minutes after anaesthesia induction. Results: The MAP during the trial was 93 ± 9 mm Hg in the intervention group and 62 ± 5 mm Hg in the control group. PV increased with up to 420 ± 180 mL in the control group and 45 ± 130 mL in the intervention group ( P  < .001). Albumin and colloid osmotic pressure decreased significantly more in the control group. MR‐proANP increased in the control group but no shedding of the glycocalyx layer was detected in either of the groups. Conclusion: Allowing mean arterial pressure to fall to 60 mm Hg during anaesthesia induction, increases the plasma volume due to reabsorption of interstitial water, with no ANP‐induced degradation of the endothelial glycocalyx.